TANTANGAN DAN PELUANG PERBANKAN SYARIAH DALAM PENGEMBANGAN USAHA KECIL DAN MENENGAH UNTUK MEMPERKUAT KESEJAHTERAAN UMAT - Maisaroh Maisaroh; Ati Sumiati (Jurnal Ilmiah Econosains, 2011)
ABSTRACT Islamic Banking of Indonesia lately grows so rapidly. The function of Islamic banking is as intermediary institution between the excess money parties (depositor) with the lacking money parties (borrower) by using a system of Islamic sharia. The operational purpose of Islamic banking is to participate actively in development process of social and economic life of the community in managing all assets for social welfare. In other side, the growth of small -medium enterprises in Indonesia are also very fast. These types of institutions are identified and proved to be the savior of the economic crisis in Indonesia. But, small and medium enterprises have difficulty constraints of capital and human resources that make these institutions are difficult to thrive. According to the operational purpose, Islamic banking and small-medium enterprises can be partners of mutual benefit. Both parties should build up a quality partnership with optimizing the role of empowerment and facilitation of the Islamic banking to small-medium enterprises using the principles of relationship, togetherness, and humanitarian. Coupled with improving the quality of human resources, services, and partnership, then the partnership is expected not only profitable for both parties, but also more broadly is expected to create social welfare for community.Keywords: Islamic Banking, Small and Medium Enterprises, Social Welfare, Empowerment